International democracy promotion in times of autocratization: From supporting to protecting democracy - Julia Leininger (German Institute of Development and Sustainability (IDOS), 2022)
The worldwide wave of autocratization is doing away with many of the democratic achievements made since 1989. Scholarship on international democracy promotion is yet to theorise how democracy can be protected from autocratization. Such a theory must account for different democratic and autocratic trajectories as well as integrate theoretical approaches from international relations and comparative politics in the study of democracy promotion. However, such a combined perspective is still missing. One reason for this is that the field lacks a clear concept of "protection" and does not yet systematically integrate evidence from democratization research. This paper addresses this research gap. It is the first attempt to develop a concept theory of democracy promotion, which includes support and protection of democracy. Coupling this with a depiction of six phases of regime change, this paper makes a second contribution: based on the proposed conceptual and theoretical integration, it generates a series of testable anchor points for further empirical analysis on what strategies are most likely to be effective during the various phases of regime change.
Keywords: 330; democracy promotion; democratization; autocratization; concept-formation